Should psychosocial factors be taken into account when developing and implementing population-level preventive programmes? - A. N. Britov; N. A. Eliseeva; A. D. Deev; E. V. Miroshnik (Кардиоваскулярная терапия и профилактика, 2012)
Aim. To assess social status and selected psychological characteristics in organised urban populations from 5 Russian regions; to compare the results with the prevalence of traditional risk factors (RFs) and chronic disease. Material and methods. In 2009-2010, representative samples of organised populations from 5 Russian cities were examined (total n=2227, 1336 women and 891 men). The questionnaires assessed socioeconomic status (SES), as well as somatic and psychological health. The assessed psychological parameters included Lifestyle Index (LI), psychological resilience mechanisms (PRM), social adaptation, sanogenic reflection, Eysenck phychoticism scale, personal moral potential, emotional burnout syndrome, Hospital Anxiety and Depression Scale (HADS), and Perceived Stress Scale (PSS). The examination included the measurement of blood pressure, heart rate, waist circumference, and hips circumference. Results. The proportion of higher-educated people ranged from 82% in Nalchik to 29,3% in Omsk. Low self-rated wealth levels were highly prevalent (from 10,4-13% to 40,4%). Arterial hypertension was registered in 1,29% and 1,64% of men and women aged 25-34 years. In people aged 65-74 years, the respective figures were 60% and 75,8%. Obesity (body mass index ≥30 kg/m2) was registered in over 50% of the participants from all social groups. Negative (pathological) levels of LI significantly correlated with the majority of somatic diseases (р<0,001) and psychological disorders (р<0,007). In women, negative PRM were significantly more prevalent than in men (р<0,007). In those aged under 50 years, the prevalence of negative PRM was lower (up to 28%) than in those aged 50-60 years (37,8%), or 60-75 years (57,7%) (р<0,001). Conclusion. The development and implementation of population-level preventive programmes should take into account not only morbidity levels and traditional RFs, but also psychosocial features of the respective population groups.